Estudo de efeitos de um extrato aquoso de farinha de casca de maracujá (Passiflora edulis f. flavicarpa) na marcação de constituintes sangüíneos com Tecnécio 99m, na morfometria das hemácias e na biodisponibilidade do radiofármaco Pertecnetato de Sódio em ratos Wistar - Rebello, Bernardo Machado (2008)
Blood constituents labelled with technetium-99m (99mTc) has been used with radiobiocomplexes in several procedures in nuclear medicine. Some natural and sintetic drugs are capable to interfere on the labeling of blood constituents with 99mTc, on the morphology of red blood cells (RBC) and on the biodistribution of radiobiocomplexes. The aim of this study was evaluate the effect of an extract of Passiflora edulis f. flavicarpa on the labeling of blood constituints with 99mTc, on the morphology of RBC and on the biodistribution of the radiopharmaceutical sodium perthecnetate in Wistar rats. On the in vitro studies the Passiflora edulis f. flavicarpa decreased significantly (p<0.05) the %ATI on plasma proteins and on the in vitro morhology of RBC, the passion fruit peel flour altered the shape and the perimeter/área ratio. On the in vivo estudies the extract did not altered the %ATI in blood constituents, and did not altered the shape of RBC. Although, on the biodistribution of the radiobiocomplex sodium perthecnetate (Na99mTcO4) this extract decreased significantly (p<0.05) the uptake in duodenum, spleen, pâncreas and blood, and increased the uptake in stomach. It can be suggested that the effects presented by this extract could be a result of some substances contained in this extract that could alter the binding of 99mTc to plasma proteins, the morphology of RBC and the biodistribution of the radiobiocomplex sodium perthecnetate. This study was multidisciplinary experimental research. It was developed with the contribution of different Departments and Services of the Hospital Universitário Pedro Ernesto of the Universidade Estadual do Rio de Janeiro